Research on Influence of Damping on the Vibration Noise of Transformer - Lihua Zhu; Jianying Hao; Lan Lu (IEEE Access, 2022)
To improve the transformer vibration analysis accuracy, a numerical vibration model of transformer, including the damping effect, is proposed in the paper. According to power transformer structure, the Rayleigh damping model is used to indicate the transformer damping effect. The damping coefficients can be got by analyzing and testing the transformer structure. The modal measurement system of the prototype is constructed and tested to improve and verify the modal analysis method, which can be used to analyze the engineering power transformer that the modal measurement should not be achieved. According to the Rayleigh damping parameters, the vibration and noise of damped and undamped transformers are calculated respectively. Then the effect of the damping on the vibration and noise can be obtained. At last, the vibration and noise of the transformer were tested and compared with the analytic results. Comprehensive analysis shows that the analysis results considering damping can be improved, and are closer to the measured results.